Prosedur Audit Konfirmasi Bank untuk Menguji Asersi Keberadaan, Keterjadian, dan Akurasi atas Kas di Bank PT NAS oleh KAP KPS - Nilam Dhawi Nariswari; Yusrina Alyani Tamimi; Kristanti Kristanti; Zidni Husnia Fachrunnisa (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2025)
This study aims to explain the bank confirmation audit procedures in testing assertions regarding the existence, occurrence, and accuracy of cash at bank accounts at PT NAS conducted by KAP Kanaka Puradiredja Suhartono. These assertions play a role in proving and ensuring that cash balances actually exist, that legitimate transactions have occurred, and that the balances in the financial statements have been recorded appropriately. The method used in this research is a descriptive qualitative approach with comparative analysis techniques, which will compare the implementation of bank confirmation procedures in the field with Auditing Standard 505 regarding External Confirmation. The data collection techniques used are participatory observation, documentation, and literature study. Based on the audit process carried out, there was a delay in receiving a reply to the confirmation letter from one of the banks, but no difference was found between the cash balance in the bank and the balance of PT NAS's financial statements. The results of this study indicate that the bank confirmation procedure for the cash in bank account of PT NAS can prove assertions regarding its existence, occurrence and accuracy.